Spondias rootstock in the formation of seedlings of the yellow mombin - Souza, Francisco (Revista Ciência Agronômica, 2019)
The aim of this study was to determine the effect of Spondias rootstock on the formation of grafted seedlings of the yellow mombin. The experiment was set up in the Experimental Area of Embrapa, in Pacajus, in the state of Ceará (CE), in a completely randomised design with four treatments (rootstocks), five replications and ten seedlings/plot. Ungrafted rootstock of S. tuberosa and of three species of mombin (S. macrocarpa, S. mombin and S. venulosa) were grown in polyethylene bags (15 x 28 cm x 0.15 mm), filled with a mixture of quartz sand + hydromorphic soil + rotted cattle manure (2:2:1, v/v).  The cleft graft was made 6 cm from the root collar of 80-day-old rootstock. The scions were taken from the apical branches of mature deciduous plants of the Itaitinga clone of the yellow mombin. After grafting, the scions were protected with transparent plastic bags (4 x 16 cm), and the seedlings remained in the nursery shaded with 50% sombrite for 64 days, when the percentage of grafts, seedlings suitable for planting, and the number of leaves and leaflets were determined. Grafting success and the percentage of seedlings suitable for planting was 90% on rootstock of S. tuberosa, S. mombin and S. venulosa, and showed no statistical difference. The greatest grafting success with seedlings suitable for planting was on S. tuberosa, S. mombin and S. venulosa. Grafting success on S. macrocarpa was extremely low due to incompatibility, and this should not be used as rootstock for the yellow mombin.